The Effectiveness of the Backfoot Shooting Technique among U-12 Students - Pangestu Rovino; Topo Yono; Ahmad Sulaiman (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
The purpose of this study was to evaluate the effectiveness of instep shooting drills for soccer players at Plalangan 03 Elementary School in the U-12 age group. Using skill tests, documentation, interviews, and observations, this research employed a case study design with a descriptive qualitative approach. Ten children who participated in soccer as an extracurricular activity served as the subjects. Data were collected through interviews with players and coaches, observations of kicking techniques, and ten shooting trials for each student. The findings revealed that students’ kicking accuracy ranged from 40% to 90%, with an average of 67%. These results indicate that although most students were able to use the instep technique effectively, issues with precision and consistency still persist. Contributing factors include a lack of fundamental skills, concentration, ball control, field conditions, and ball quality. In conclusion, instep shooting drills are beneficial for improving basic kicking skills. However, more structured technique training, accuracy development, and enhanced coordination and physical strength are necessary for further improvement. Coaches and extracurricular program managers are encouraged to use the findings of this study as a reference in developing training plans for young soccer players.